2017
DOI: 10.1523/jneurosci.2235-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Differentially Regulates Synaptic Plasticity in the Hippocampus and Spinal Cord by Microglia-Dependent Mechanisms after Peripheral Nerve Injury

Abstract: Clinical studies show that chronic pain is accompanied by memory deficits and reduction in hippocampal volume. Experimental studies show that spared nerve injury (SNI) of the sciatic nerve induces long-term potentiation (LTP) at C-fiber synapses in spinal dorsal horn, but impairs LTP in the hippocampus. The opposite changes may contribute to neuropathic pain and memory deficits, respectively. However, the cellular and molecular mechanisms underlying the functional synaptic changes are unclear. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 7 publications
2
53
0
2
Order By: Relevance
“…A mouse model of chronic constriction injury of the sciatic nerve reduced neurite length in GABA neurons within lamina II of the spinal cord [50]. Another group observed that following spared nerve injury, there were decreases in the number of branches and neurite length of hippocampal neurons but increases in spinal dorsal horn neurons [51]. Together these studies, along with those reported here, suggest adaptations of the central nervous system to chronic pain culminate in alteration of the neuronal cytoarchitecture.…”
Section: Discussionsupporting
confidence: 74%
“…A mouse model of chronic constriction injury of the sciatic nerve reduced neurite length in GABA neurons within lamina II of the spinal cord [50]. Another group observed that following spared nerve injury, there were decreases in the number of branches and neurite length of hippocampal neurons but increases in spinal dorsal horn neurons [51]. Together these studies, along with those reported here, suggest adaptations of the central nervous system to chronic pain culminate in alteration of the neuronal cytoarchitecture.…”
Section: Discussionsupporting
confidence: 74%
“…We also found that ReaChR is widely expressed in different brain regions such as the hippocampus and cortex. Therefore, CX3CR1 creER/+ : R26 LSL-ReaChR/+ transgenic mice will be a useful tool to study supraspinal microglia in brain function, such as pain-related comorbidity 53 , memory 54 , and epilepsy 55 There are two potential consequences after ReaChR activation, including membrane depolarization and Ca 2+ elevation. Currently, we know little about the function of membrane potential alterations in microglia function.…”
Section: Discussionmentioning
confidence: 99%
“…For the requirements of the tested segments, protrusions on successive dendritic segments within 50–130 µm away from the centre of the soma were examined regardless of whether they were from primary, secondary or tertiary dendritic branches (Liu et al . 2017; Pyronneau et al . 2017).…”
Section: Methodsmentioning
confidence: 99%